ANALISIS PENGARUH SANITASI DAN ANGKA KEMATIAN IBU TERHADAP INDEKS PEMBANGUNAN MANUSIA DI SUMATERA UTARA - Natasya Santa Elisabeth Siahaan (Quantitative Economics Journal, 2018)
This study aims to determine the Inadequate Sanitation Influence and Maternal Mortality Rate on Human Development Index (HDI) in North Sumatra. The analytical tool used in this study is the Panel Regression Analysis through the Panel Least Square (PLS) method using the Eviews 10. program. The data used is a panel data consisting of 33 districts and cities in North Sumatra from 2014 to 2016. The result shows that improper sanitation and maternal mortality have a negative and significant effect on the human development index in North Sumatra. While simultaneously, improper sanitation and maternal mortality rates have a significant effect on the human development index in North Sumatra.